Elementary sulfur compound cellulose-based spiral porous microspheres as well as preparation and application thereof
The preparation of cellulose-based helical porous microspheres through membrane emulsification method and etching carbonization technology has solved the problem of polysulfide shuttle effect in lithium-sulfur batteries, and improved the cycle stability and discharge specific capacity of the battery.
Patent Information
- Application Number
- CN202311748867.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2025-06-20
AI Technical Summary
The shuttle effect of polysulfides in lithium-sulfur batteries leads to rapid capacity decay and excessive use of electrolytes in actual applications, limiting the cycle life and energy density of the battery.
By adopting membrane emulsification method and etching carbonization technology, cellulose-based helical porous microspheres were prepared, and polysulfides dissolved in physical domains were used to alleviate the shuttle effect.
The long cycle stability of lithium-sulfur batteries and the discharge specific capacity of the battery are improved, maintaining the advantages of high capacity and low cost.
Smart Images

Figure HDA0004615160520000011 
Figure HDA0004615160520000012 
Figure HDA0004615160520000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and particularly relates to a preparation method and application of a sulfur element composite cellulose-based helical porous microsphere. Background Art
[0002] With the development of economy and the progress of lifestyle, the demand for energy by human beings has been continuously increasing. However, the long-term use of fossil energy has brought negative problems such as environmental pollution and greenhouse effect, thus giving rise to the demand for renewable energy technologies. Secondary batteries can store the intermittent electric energy converted from solar energy and wind energy. Therefore, continuously developing secondary batteries with excellent performance is the key to promoting the application of renewable energy. Among various new secondary battery systems, lithium metal batteries with metallic lithium as the negative electrode and conversion-type electrode materials as the positive electrode are one of the most widely used and studied chemical battery systems at present. Sulfur element has the advantages of abundant reserves, low price, non-toxic and harmless, etc. The lithium-sulfur battery composed of it and metallic lithium has a theoretical specific capacity as high as 2600 Wh / kg, and is expected to replace lithium-ion batteries to become the next-generation lithium metal battery with the broadest application prospects and research potential.
[0003] However, their large-scale practical applications still face challenges, such as the poor conductivity of sulfur and solid discharge products (Li2S / Li2S2), and the large volume change (about 80%) of the sulfur positive electrode during the cycling process. The operation of Li-S batteries involves solid-liquid-solid continuous reactions during discharging and charging processes, and generates a series of polysulfide ions that are soluble in organic electrolytes. Therefore, for practical Li-S batteries, a more serious problem is the soluble Li2S n shuttling from the cathode side to the anode side to form non-reusable solid Li2S2 / Li2S, which leads to the so-called "shuttle effect". This limits the rapid capacity decay (short cycle life) of practical applications and the excessive use of electrolytes (the energy density is much lower than the theoretical value). Therefore, how to alleviate the shuttle effect of polysulfides is a basic scientific problem still existing in lithium-sulfur batteries. Physical confinement mainly uses porous carbon and chemical anchoring polar matrices, which are usually used to inhibit the shuttle effect.
[0004] In recent years, porous carbon spheres, as a method of physical confinement, have received much attention. Cellulose nanocrystals, as a renewable green energy source, can lay the foundation for the preparation of porous carbon due to the chiral nematic structure therein. By using the membrane emulsification method to prepare cellulose-based helical microspheres, the cellulose-based helical carbon spheres can be obtained by high-temperature heat treatment of the helical microspheres under an inert atmosphere condition. After etching the cellulose-based helical carbon spheres, the cellulose-based helical porous carbon spheres can be obtained. The carbon spheres are characterized by having a large specific surface area, providing rich reaction sites for sulfur; at the same time, the intricate pores in the carbon spheres have a physical confinement effect on the dissolved polysulfides, which can alleviate the "shuttle effect" of polysulfides. The present invention uses green and sustainable cellulose nanocrystals as the matrix, and the preparation method is simple, green and environmentally friendly; the prepared carbon material used as the cathode material of a lithium-sulfur battery has a high discharge specific capacity and capacity retention rate. Summary of the Invention
[0005] The purpose of the present invention is to provide a sulfur-composite cellulose-based helical porous microsphere and its preparation and application. Through reasonable nanostructure design and construction, the prepared helical microspheres have a large specific surface area, providing rich reaction sites for sulfur; at the same time, the intricate pores in the carbon spheres have a physical confinement effect on the dissolved polysulfides, which can alleviate the "shuttle effect" of polysulfides, thereby suppressing the shuttle effect in the sulfur cathode and improving the long-term cycling stability of the battery.
[0006] A sulfur-composite cellulose-based helical porous microsphere material, characterized in that the sulfur-composite cellulose-based helical porous microsphere material uses cellulose nanocrystals with a chiral nematic structure as a template, and after water-in-oil and thermal dehydration, self-assembles into helical microspheres, and sulfur is distributed in the voids between the self-assembled helices of cellulose nanocrystals. The carbon content in the composite material is 10% - 40%, and the sulfur content is 40% - 80%;
[0007] For the cellulose microsphere material with the helical structure, the micropores in the carbon material are 1.48 - 7 nm, the specific surface area is 800 - 1400 m 2 ·g -1 , and the pore volume is 0.8 - 2 cm 3 g -1 .
[0008] A preparation method of a sulfur-composite cellulose-based helical porous microsphere material. After uniformly mixing the cellulose nanocrystal dispersion liquid with a silane coupling agent, it is injected into the oil phase through a membrane emulsification connector connected to a syringe. The obtained microspheres are dehydrated and dried, and then carbonized. After etching and heat treatment for sulfur loading, the material is obtained, including the following steps:
[0009] (1) Preparation of cellulose nanocrystal / tetramethoxysilane helical microspheres: After uniformly mixing cellulose nanocrystals and tetramethoxysilane with a mass ratio of 100:2, they were injected into a homogeneous oil phase with a mass ratio of Span 80 to hexadecane of 5:100 through a membrane emulsification connector connected to a syringe. After ethanol washing and dehydration and drying, spherical cellulose-based helical microspheres were obtained.
[0010] (2) Carbonization: The cellulose helical microspheres prepared in step (1) were placed in a tube furnace and pyrolytically carbonized at high temperature under an argon or nitrogen atmosphere to obtain carbonized cellulose helical microspheres.
[0011] (3) Etching: The carbonized cellulose helical microspheres prepared in step (2) were dispersed in a concentrated sodium hydroxide aqueous solution and reacted under heating conditions to etch away the silica template layer. The product was obtained by suction filtration, washing, and drying to obtain a porous cellulose-based helical microsphere material.
[0012] (4) Sulfur compounding: The porous helical microsphere material prepared in step (4) and sublimed sulfur were ground according to a mass ratio of 1:2 - 6, transferred to a sealed bottle, and heat-treated to carry sulfur to obtain a sulfur-compounded porous cellulose-based helical microsphere material.
[0013] Specifically, the preparation of the cellulose nanocrystal / tetramethoxysilane helical microspheres in step (1) is to slowly add 2 mL of tetramethylsilane (TMOS) drop by drop to 30 mL of an aqueous solution of cellulose nanocrystals (CNC). The compounding was carried out at a temperature of 25 °C and stirred at 400 r·min -1 for two hours and then sucked into the syringe. The CNC / TMOS composite liquid was pressed into the continuous phase of hexadecane containing 2 wt% Span 80 by an injection pump, and the continuous phase was stirred at a constant speed during this process. The obtained CNC / TMOS microdroplets formed small balls through thermal curing dehydration, and were screened through a 500-mesh sieve to obtain cellulose-based helical microspheres with a diameter of 30 μm.
[0014] Specifically, the preparation of the cellulose-based helical porous carbon in step (2) is to carbonize 5 g of CNC / TMOS microspheres at 800 °C under a protective atmosphere of high-purity nitrogen or argon, and the gas flow rate is 50 - 200 ml·min -1 , and 2.8 g of C / SiO2 microspheres were obtained.
[0015] The concentration of sodium hydroxide in step (3) is 1 - 6 mol·L -1 ;
[0016] The protective atmosphere in step (4) is high-purity argon or high-purity nitrogen, and the gas flow rate is 20 - 100 ml·min -1, the heat treatment temperature is 140°C to 160°C, and the treatment time is 12 to 24 hours;
[0017] The present invention uses a membrane emulsification method and an etching carbonization technique to prepare fiber-based helical porous microspheres, which have a high initial discharge specific capacity and a stable capacity retention rate when used as the positive electrode material of a lithium-sulfur battery.
[0018] Using the membrane emulsification method, CNC / TMOS helical microspheres with uniform particle size and dispersion are constructed. However, during the preparation process, due to the surface tension of the hexadecane liquid, micro-droplets are not easily formed. In addition, these micro-droplets cannot exist stably after formation. To solve the above problems, Span 80 is introduced into the continuous phase composed of hexadecane. On the one hand, as a surfactant, Span 80 weakens the interfacial resistance when the CNC / TMOS droplets are pressed into hexadecane, enabling the simple and rapid formation of micro-droplets; on the other hand, Span 80 can be used as an emulsifier to stabilize the existence of CNC / TMOS micro-droplets in the continuous phase. These micro-droplets are further dehydrated by heat to form CNC / TMOS helical microspheres. Finally, we obtain a porous cellulose-based helical microsphere with a large surface area, and this porous cellulose-based helical microsphere can be loaded with elemental sulfur for use as the positive electrode material of a lithium-sulfur battery. Here, the positive electrode material derived from cellulose nanocrystals can simultaneously exhibit a large specific surface area and a rich pore structure. The porous cellulose-based helical microspheres after carbonization etching provide multiple-site choices for the loading of elemental sulfur, which helps to weaken the shuttle effect of sulfur. A representative porous helical cellulose-based microsphere is prepared by a convenient method, and good dispersion and uniformity are achieved by adjusting the proportion of Span 80 and the stirring speed. This method is superior to the preparation of other positive electrode materials in terms of secondary pollution, high cost, and complex reaction process.
[0019] The technical advantages of the present invention:
[0020] Cellulose-based porous helical microspheres are prepared by using a membrane emulsification method and an etching carbonization technique; a sulfur positive electrode with a large specific surface area and a high sulfur loading is prepared; the preparation process of this material is easy to operate and has a low cost; this positive electrode material has the advantages of low cost and sustainability.
[0021] Using sustainable cellulose as the matrix, cellulose-based porous helical microspheres are prepared by a membrane emulsification method and an etching carbonization technique; the emulsification of Span 80 reduces the interfacial resistance of the continuous phase and enables the stable existence of micro-droplets; the size of the microsphere diameter can be adjusted.
[0022] The present invention uses green and sustainable cellulose nanocrystals / tetramethylsilane as the matrix; sodium hydroxide or hydrofluoric acid as the etching solvent; the porous helical microspheres have a high specific surface area, high dispersibility, and the ability to load elemental sulfur.
[0023] The carbon spheres have a large specific surface area, providing abundant reaction sites for sulfur. At the same time, the intricate pores within the carbon spheres have a physical confinement effect on the dissolved polysulfides, which can alleviate the "shuttle effect" of polysulfides. In the present invention, green and sustainable cellulose nanocrystals are used as the matrix, and the preparation method is simple, green, and environmentally friendly. The prepared carbon material used as the cathode material of a lithium-sulfur battery has a high discharge specific capacity and capacity retention rate. Description of the Drawings
[0024] Figure 1 It is a preparation diagram of CNC / TMOS microdroplets. The pore diameter of the membrane emulsification connector is 300 nm. The mass ratio of the oil phase (hexadecane / Span 80) to the water phase (CNC / TMOS) is 4:1. After processing 15 mL of the dispersed phase each time, the droplets are collected;
[0025] Figure 2 It is a polarized light microscope image of CNC / TMOS microdroplets. Under cross-polarized light, the microdroplets exhibit anisotropic birefringence phenomena, with relatively uniform sizes, approximately between 20 and 50 μm;
[0026] Figure 3 It is a polarized light microscope image of CNC / TMOS microspheres. Through the POM image, it can be seen that the microspheres obtained by treating the microdroplets through thermal dehydration have uniform sizes, approximately around 30 μm, and good monodispersity;
[0027] Figure 4 It is a polarized light microscope image of CNC / TMOS microspheres. Through the high-magnification POM image, it can be seen that there are fingerprint-like textures and helical structures on the surface of the microspheres, indicating that the microspheres retain the chiral nematic structure of cellulose nanocrystals;
[0028] Figure 5 It is a scanning electron microscope image of CNC / TMOS microspheres. It is observed that the surface of the microspheres is relatively rough and there are depressions. This structure is beneficial for the composite of elemental sulfur and it to be used as the cathode material of a battery;
[0029] Figure 6 It is the nitrogen adsorption-desorption isotherm and pore size distribution curve of cellulose-based porous helical carbon spheres. The obtained carbon material shows an isotherm with type-IV characteristics and significant hysteresis, indicating that mesopores are introduced into the sample. The specific surface area and pore volume are 1330.69 ± 10 m 2 ·g -1 and 1.46 ± 0.06 cm 3 ·g -1 ;
[0030] Figure 7It is the scanning electron microscope image of the cellulose-based porous helical carbon spheres of Example 1. It can be observed that the surface of the carbon spheres is sunken, and the intricate pores inside the carbon spheres have a physical confinement effect on the dissolved polysulfides, which can alleviate the "shuttle effect" of polysulfides;
[0031] Figure 8 It is the cycle diagram of the battery specific capacity of Example 1.
[0032] Figure 9 It is the scanning electron microscope image of the cellulose-based porous helical carbon spheres of Comparative Example 1.
[0033] Figure 10 It is the scanning electron microscope image of the cellulose-based porous helical carbon spheres of Comparative Example 2. Specific Embodiments
[0034] The following examples are further descriptions of the present invention rather than limiting the scope of the present invention.
[0035] Example 1
[0036] Prepare cellulose nanocrystals / tetramethoxysilane helical microspheres: At room temperature, 4 mL of tetramethylsilane (TMOS) was slowly added dropwise to 30 mL of a 5 wt.% cellulose nanocrystal (CNC) suspension for compounding (the mass ratio of cellulose nanocrystals to silane coupling agent is 1:27), and stirred at 400 r·min -1 for 2 h to obtain a CNC / TMOS composite solution, which was sucked into a 30 mL syringe. The CNC / TMOS composite solution was pressed into 100 mL of a continuous phase of hexadecane containing 2 wt.% Span 80 through a membrane emulsification connector (pore diameter of 10 μm), and the continuous phase was stirred at a constant speed of 500 r·min -1 during this process. The membrane emulsification connector used was the PC10N type SPG membrane emulsification connector of As one manufacturer. The preparation process of CNC / TMOS is as Figure 1 shown, that is, after connecting the syringe to the membrane emulsification connector, the membrane emulsification connector was placed below the liquid level of the continuous phase to enable continuous and stable generation of microdroplets, as Figure 2 shown, and it was observed that the microdroplets showed birefringence under POM (polarizing light microscope).
[0037] The obtained CNC / TMOS microdroplets formed small balls through thermal curing dehydration at 30 °C, passed through a 500-mesh sieve, and the small balls passing through the 500-mesh sieve were collected to obtain cellulose-based helical microspheres with a diameter less than 30 μm, as Figure 3 , 4 shown. It was observed under POM that it had good dispersibility and fingerprint-like textures on the surface; observed by SEM, the surface of the microspheres was relatively rough and there were depressions, asFigure 5 As shown, the rod-shaped cellulose nanofibrils form a chiral nematic structure through self-assembly, and the rod-shaped cellulose nanofibrils are arranged in a helix.
[0038] 5 g of CNC / TMOS microspheres were carbonized under argon at 800 °C with a gas flow rate of 100 ml / min, and the temperature was raised from room temperature to 800 °C at a heating rate of 2 °C·min -1 and held at this temperature for 3 h; 2.8 g of C / SiO2 microspheres were obtained. Then, the C / SiO2 microspheres were etched with NaOH solution. The carbonized product was placed in 200 ml of 4 mol·L -1 aqueous sodium hydroxide solution, and reacted at 90 °C for 6 h to etch silicon dioxide. After filtration, washing and drying, black porous carbon spheres, namely cellulose-based helical porous carbon spheres, about 1.5 g, with a yield of about 35% were obtained. The specific surface area was measured. From the nitrogen adsorption-desorption isotherm, the obtained carbon material showed an isotherm with type-IV characteristics and significant hysteresis, indicating the introduction of mesopores in the sample. The BET and pore volume were 1330.69 ± 10 m 2 ·g -1 and 1.46 ± 0.06 cm 3 ·g -1 , as Figure 6 shown. The obtained cellulose-based porous helical carbon spheres were characterized by scanning electron microscopy, and it was observed that the surface depressions of the carbon spheres increased and the depressions became more numerous, as Figure 7 shown. The carbon spheres obtained after carbonization maintained the chiral nematic structure of cellulose nanocrystals, that is, the rod-shaped cellulose nanofibrils after carbonization were still arranged in a helix.
[0039] 0.1 g of cellulose-based helical porous carbon spheres were taken, ground with 0.4 g of sublimed sulfur, transferred to a sealed glass bottle, and heat-treated at 155 °C for 10 h to obtain a sulfur-carbon composite.
[0040] Take 0.16 g of it, add 0.02 g of conductive carbon and 0.40 g of a 5.wt% polyvinylidene fluoride (PVDF) solution, with the solvent being N-methylpyrrolidone. Additionally, add approximately 0.2 mL of N-methylpyrrolidone solvent. After grinding for 1 h, a viscous slurry is obtained, which is blade-coated onto carbon-coated aluminum foil with a 200-micron blade to form a film, and the slurry thickness is approximately 250 μm. Dry overnight at 60 °C, cut into circular discs with a diameter of 10 cm, weigh them, and dry in vacuum at 55 °C for 24 h. Using this electrode as the positive electrode, a lithium sheet as the negative electrode, a Celgard 2325 cellulose membrane as the separator, a 1 M lithium bis(trifluoromethanesulfonyl)imide solution (LITFSI) as the electrolyte, 0.2 M lithium nitrate as an additive, and a mixed solution of 1,3-dioxolane (DOL) and dimethyl ether (DME) (volume ratio 1:1) as the solvent, assemble a CR2016-type battery and conduct charge-discharge tests at 0.1C and 1C rates; at a 0.1C rate, the initial charge-discharge capacity is 1402.5 mAh / g; after 350 cycles at a 1C rate, the capacity is 646.7 mAh / g; the specific capacity cycle diagram of the battery in the comparative example is as Figure 8 shown.
[0041] As Figure 8 The described embodiments are the preferred embodiments of the present invention, but the present invention is not limited to the above embodiments. Without departing from the essential content of the present invention, any obvious improvements, substitutions, or variations that those skilled in the art can make all fall within the protection scope of the present invention.
[0042] Comparative Example 1:
[0043] The process and conditions for preparing the cellulose-based helical microspheres are the same as those in Example 1;
[0044] The difference lies in the screening process. The obtained CNC / TMOS microdroplets form small spheres through thermal curing dehydration at 30 °C and are screened through a 100-mesh sieve to obtain cellulose-based helical microspheres with a diameter of less than about 150 μm.
[0045] The subsequent processes and conditions of carbonization, etching, and sulfur loading are the same as those in Example 1;
[0046] Perform SEM tests on the porous carbon spheres obtained by screening through a 100-mesh sieve (the process and conditions are the same as those in Example 1). As Figure 9 shown, the carbon spheres obtained in Comparative Example 1 have a larger diameter, approximately 150 μm. This will cause sublimated sulfur to not easily enter the internal pores of the spheres, so the physical confinement effect on sulfur is reduced, resulting in a large amount of polysulfides dissolving out and the cycle stability of the battery becoming poor.
[0047] Comparative Example 2:
[0048] The process and conditions for preparing cellulose nanocrystals / tetramethoxysilane helical microspheres are the same as those in Example 1;
[0049] The difference lies in the process of preparing cellulose helical microspheres: The obtained CNC / TMOS microdroplets form small spheres through thermal curing dehydration at 50°C. Screening is carried out through a 100-mesh sieve to obtain cellulose-based helical microspheres with a diameter less than 150 μm.
[0050] As Figure 10 Scanning electron microscope images of cellulose-based porous helical carbon spheres can be obtained, and it can be observed that the surface depressions of the carbon spheres are enlarged.
Claims
1. A preparation method of sulfur composite cellulose-based helical porous carbon spheres, characterized in that, It includes the following steps: Step 1: Add a silane coupling agent to the cellulose nanocrystal suspension and stir evenly. Step 2: Press the cellulose nanocrystal composite silane coupling agent through the pores of a membrane emulsification connector (or membrane emulsifier) into hexadecane containing span 80, and recover the generated cellulose helical microspheres. Step 3: Calcinate the cellulose helical microspheres obtained in Step 2 in an inert atmosphere to obtain cellulose-based helical carbon spheres. Step 4: Add the cellulose-based helical carbon spheres obtained in Step 3 to an etching solution for etching, and then wash away the residual etching solution with deionized water and filter to collect the cellulose-based porous helical carbon spheres. Step 5: Composite the porous cellulose nanocrystal helical microspheres obtained in Step 4 with sulfur.
2. The preparation method according to claim 1, characterized in that: In Step 1, the mass fraction of cellulose nanocrystals in the cellulose nanocrystal suspension is 1% - 6% (more preferably, 3% - 5%); the mass ratio of cellulose nanocrystals to the silane coupling agent is 1:20 - 1:35 (more preferably, 1:25 - 1:30); the stirring speed is 100 - 1000 rpm (more preferably, 400 - 700 rpm); the time is 1 - 5 h. The mass ratio of Span 80 to hexadecane described in Step 2 is 1:100 to 5:100 (more preferably, 2:100 to 3:100); wherein Span 80 and hexadecane are stirred during use, and the stirring rate is set to 100 to 1000 r·min -1 (more preferably, 300 to 600 r·min -1 ).
3. The preparation method according to claim 1, characterized in that: The silane coupling agent described in Step 1 includes but is not limited to one or more of tetramethoxysilane, tetraethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyltris(β-methoxyethoxy)silane, butadienyltriethoxysilane, isobutyltriethoxysilane, etc. (more preferably, tetramethoxysilane).
4. The preparation method of the helical microspheres according to claim 1, characterized in that, Use a syringe to press the cellulose nanocrystal composite tetramethoxysilane through the pores of a membrane emulsification connector into hexadecane containing span 80. After carbonization and etching of the obtained cellulose-based helical microspheres and composite with elemental sulfur, a porous cellulose-based microsphere used as a sulfur cathode is obtained. The specific steps are as follows: 1) Synthesis of cellulose-based microspheres: Use a syringe to press the cellulose nanocrystal composite tetramethylsilane suspension through a membrane emulsification connector with a pore diameter of 10 microns into hexadecane containing span 80, where the volume ratio of the cellulose nanocrystal / silane coupling agent suspension to hexadecane / span 80 is 1:2 - 1:5 (more preferably, 1:3 - 1:3.5) to obtain cellulose-based helical microspheres. 2) Carbonization: Place the obtained cellulose microspheres in a tube furnace and pyrolytically carbonize them at high temperature under an argon and / or nitrogen atmosphere to obtain carbonized microspheres. 3) Etching: Disperse the obtained carbonized microspheres into a concentrated sodium hydroxide aqueous solution and react under heating conditions to etch away the silica template. The product is filtered, washed, and dried to obtain porous cellulose nanocrystal helical microspheres. 4) Sulfur composite: Grind the prepared porous cellulose nanocrystal helical microspheres and sublimed sulfur in a mass ratio of 1:2 - 6, transfer them to a sealed bottle, and perform heat treatment to load sulfur to obtain a sulfur@carbon sphere composite material.
5. The preparation method of the helical microspheres according to claim 4, characterized in that: In the step 1), 30 mL of cellulose nanocrystal / tetramethylsilane (CNC / TMOS) composite solution is pressed into a 60-150 mL (more preferably 80-120 mL) hexadecane solution containing 2 wt.% Span 80 through a membrane emulsification connector, and the continuous phase is stirred continuously at 100-800 r·min -1 (more preferably 300-500 r·min -1 ). Finally, the obtained CNC / TMOS microdroplets form small spheres through thermal curing dehydration at 25-40 °C (more preferably 30-35 °C). Screening is carried out through a 300-500 (more preferably 500 mesh) mesh sieve, and cellulose-based helical microspheres with a diameter less than 30-50 μm (more preferably less than 30 μm) are collected; when the mesh number of the sieve in the above screening process is different and other reaction conditions are kept unchanged, cellulose-based microspheres with different diameters can be obtained.
6. The preparation method of the sulfur composite porous helical cellulose-based microspheres according to claim 4, characterized in that: In the step 2), the protective atmosphere in the tubular furnace is high-purity nitrogen and / or argon, the gas flow rate is 50-200 ml / min (preferably 100-200 ml / min), the carbonization temperature is 600°C-900°C (preferably 700°C-900°C), the carbonization time is 1-10 h (preferably 3-5 h), and the heating rate from room temperature to the carbonization temperature is 1-10°C / min (preferably 2-5°C / min).
7. The preparation method of the sulfur composite porous helical cellulose-based microspheres according to claim 4, characterized in that: In the step 3), the concentration of sodium hydroxide is 1-6 mol / L (preferably 3-6 mol / L); the reaction is carried out at 60-90°C for 4-8 h.
8. The preparation method of the sulfur composite porous helical cellulose-based microspheres according to claim 4, characterized in that: In the step 4), the heat treatment temperature is 140°C-160°C (more preferably 150°C-160°C), and the treatment time is 6-12 h (more preferably 8-10 h).
9. A sulfur composite cellulose-based helical porous microsphere prepared by the preparation method according to any one of claims 1-8.
10. An application of the sulfur composite cellulose-based helical porous microsphere according to claim 9 as an active ingredient in a cathode material for lithium-sulfur / ion batteries.